Assessing Consumer Behavior in the Wine Industry and Its Consequences for Wineries: A Case Study of a Spanish Company - Muñoz, Rosa M.; Fernández, M. Valle; Salinero, Maria Yolanda (Frontiers in Psychology, 2019)
The widening gap between production and domestic consumption has led Spain to become the country with the largest volume of wine exports, of which it has a global market share of 20.5%. Wineries in Spain have, in recent years, undergone important transformation and modernization processes, while their customers have simultaneously acquired more power than ever before owing to both the availability of information and the technological means required to access that information. The objectives of this paper are the following. We first wish to analyze current wine consumer behavior in an attempt to discover indicators associated with exploratory behavior, i.e., the willingness to try new and innovative products for the first time. We also attempt to understand the extent of wine consumers’ demands in this new digital and technological world. The second goal is to analyze the changes that have taken place in the wine industry, which have come about as a result of the evolution of consumers’ expectations and demands. The customer accordingly now plays a new role in this new quick change scenario, which involves aspects such as the intensive use of technology, advances in communication, digital transformation, etc. We consider that this could affect some aspects of business and have, therefore, chosen to analyze one of the most advanced Spanish wineries in order to examine its entrepreneurial orientation, strategy and level of technological and digital transformation when linked to adaptation to this new consumer behavior. The results and conclusions obtained will allow us to apply our findings in future research, during which we intend to expand our studies to wineries from other regions and countries.